Buccal swab as a reliable predictor for X inactivation ratio in inaccessible tissues. Issue 11 (28th July 2015) - de Hoon, Bas; Monkhorst, Kim; Riegman, Peter; Laven, Joop S E; Gribnau, Joost
Abstract : Background: As a result of the epigenetic phenomenon of X chromosome inactivation (XCI) every woman is a mosaic of cells with either an inactive paternal X chromosome or an inactive maternal X chromosome. The ratio between inactive paternal and maternal X chromosomes is different for every female individual, and can influence an X-encoded trait or disease. A multitude of X linked conditions is known, and for many of them it is recognised that the phenotype in affected female carriers of the causative mutation is modulated by the XCI ratio. To predict disease severity an XCI ratio is usually determined in peripheral blood samples. However, the correlation between XCI ratios in peripheral blood and disease affected tissues, that are often inaccessible, is poorly understood. Here, we tested several tissues obtained from autopsies of 12 female individuals for patch size and XCI ratio. Methods: XCI ratios were analysed using methyl-sensitive PCR-based assays for the AR, PCSK1N and SLITRK4 loci. XCI patch size was analysed by testing the XCI ratio of tissue samples with decreasing size. Results: XCI patch size was analysed for liver, muscle, ovary and brain samples and was found too small to confound testing for XCI ratio in these tissues. XCI ratios were determined in the easily accessible tissues, blood, buccal epithelium and hair follicle, and compared with ratios in several inaccessible tissues. Conclusions: Buccal epithelium is preferable over peripheral blood for predicting XCI ratios of inaccessible tissues. Ovary is the only inaccessible tissue showing a poor correlation to blood and buccal epithelium, but has a good correlation to hair follicle instead.